Including unpublished surveys in reviews on Chagas disease in Mexico - Pierre Buekens; Jorge López-Cárdenas; Eric Dumonteil; Nicolas Padilla-Raygoza (Public Health Reviews, 2020)
Abstract A consequence of the late awareness of Chagas disease in North America is that many early studies were never published in peer-reviewed journals and are not easily accessible for inclusion in systematic reviews. We reviewed data from the state of Guanajuato, Mexico, as an illustration. Three population-based surveys have been performed between 1991 and 2002 and were never fully published. Systematic reviews should recognize this publication bias.